METODE BERCERITA MELALUI GAMBAR MENGEMBANGAKAN KREATIVITAS USIA 5-6 TAHUN PAUD SPNF SKB - Anak Agung Rai Tirtawati Agung Rai; I Gde Suryawan; I Made Luwih (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood is a child who is in the golden age that must be optimized properly so that it requires teachers to choose the best method, especially to stimulate children's creative abilities. the next generation of intelligent, creative and character. This research is a type of classroom action research (CAR). The steps for learning the story method with pictures according to the plans that have been prepared with three cycles of each cycle according to the theme, namely learning I with the theme Pets/Chickens, the results show very well-developed children (BSB) as many as 14 people (82.4 %) and Developing According to Expectations 3 people (17.6%). Learning II with the theme of Pets/Cats the results showed 15 children (88.2%) developed very well and 2 (11.8%) developed according to expectations. Learning III with the theme Pets / Pigeons the overall results from the aspect of creativity showed that children who were very well developed (BSB) were 17 people (100%). The impact of the story-with-picture method on the development of creativity in children aged 5-6 years, namely religious and moral values; gross and fine motor physique; Language; cognitive; emotional social; and art